O problema da ordem social na obra de Adam Smith - Ivan Prates Sternick (2021)
In the present thesis, we analyse the problem of the social order in the work of Adam Smith. In its three chapters, we explore the sense in which Smith develops the idea of society as a political category of its own, endowed with a moral content and rules relatively independent of the ecclesiastical authority and of the will of the prince or sovereign, which enables him to further elaborate a representation of the social order out of the economic and the moral. Thus, we examine three distinct, though interdependent, aspects of his thought: his ethics, jurisprudence and political economy. In the first chapter, we investigate how his conception of the human being and of sociability lays the foundation for a representation of the social as a moral order, grounded on sympathy and on the self-regulation of the passions by conscience. We seek to show how this conception of the moral order allows him to bestow an ethical status to the sociability of self-love, based on human needs and interests, which integrates the core of his conception of the social order. In the second chapter, we stress the insufficiency of the moral order to solve the problem of social conflict, and explore his conception of the civil order by analysing his theory of justice, authority and obligation. We endearvour to show that Smith’s theory of law is secular and immanent, and that he explains civil obligation through the principles of authority and public utility, in contrast with the theories of the social contract. Lastly, in the third chapter, we investigate his conception of the division of labour and capital as a spontaneous process from which emerges the social order as a “system of natural liberty”. We also seek to show that, though the order emerging from the “market” is, for Smith, by nature, a free, fair and peaceful form of social organization, it inevitably comprises contradictions and the possibility of corruption, and thus in practice it incorporates violence and conflict.